Kritik Asas Non-Diskriminatif Terhadap Regulasi dalam Pasal 76c UU Nomor 35 Tahun 2014 tentang Perlindungan Anak Korban Bullying (Perundungan) - Seno, Ahmad Farhan Haryo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the conformity of Law Number 35 of 2014 with the principle of non-discrimination in the practice of handling children who are victims of bullying. This research employs a quantitative method, and the research design is library research. The results of the study in the first discussion indicate that, based on an analysis of Article 76C of Law Number 35 of 2014, several findings were obtained. Article 76C of Law Number 35 of 2014 has normatively provided legal protection for child victims of bullying, as bullying is categorized as a form of violence against children, both physically and psychologically. This regulation has a broad scope of protection because it not only holds perpetrators accountable but also parties who participate in acts of bullying against children. Thus, it can be concluded that Article 76C of Law Number 35 of 2014 emphasizes the prohibition of all forms of violence against children, including bullying, as a manifestation of legal protection for child victims. This regulation provides a legal basis for law enforcement and prevention against perpetrators of bullying and affirms the obligations of the state, society, and parents to guarantee children’s rights to safety and dignified treatment. However, the effectiveness of protection for children still depends on the consistency of law enforcement and fair and non-discriminatory implementation in practice.The results of the second discussion, based on the analysis above, conclude that with regard to the principle of non-discrimination, several provisions in Law Number 35 of 2014, particularly those related to Article 76C and its sanctioning articles, are not yet fully aligned with indicators of non-discrimination. Based on the above discussion, Article 76C of Law Number 35 of 2014 is considered not fully in line with the non-discriminatory principle because the sanctions stipulated in Article 76C have not entirely reflected the indicators of the non-discriminatory principle.